The Imagined Community in Bankim Chatterjee’s The Abbey of Bliss - Md. Nuruddin Pier Shihab (UIN Syarif Hidayatullah Jakarta, 2024)
This paper focuses on Bankim Chatterjee’s framework of nationalism in The Abbey of Bliss. Bankim’s dream of a nation-state for the Hindus is visible in the novel. On the other hand, Bankim’s docile position against the British imperialist power is visible too. This paper examines Bankim’s ambivalence as a colonial writer. From the postcolonial perspective, this paper tries to interpret Bankim’s position. He also gives a framework of community that works for the establishment of the admired nation-state. In this paper, this community is regarded as Bankim’s imagined community. The framework of nationalism Bankim provides in the novel is an amalgamation of the European framework and his thoughts. This is why this paper claims his framework is a hybrid one. This paper finds that Bankim’s framework has its strengths and weaknesses. This study tries to point out some of these strengths and weaknesses as a model of a nation-state.